Management of angioedema without urticaria in the emergency department. (December 2014) - Pedrosa, Maria; Prieto-García, Alicia; Sala-Cunill, Anna; on Behalf of the Spanish Group for the Study of Bradykinin-Mediated Angioedema (SGBA) and the Spanish Committee of Cutaneous Allergy (CCA); Members of the Spanish Group for the Study of Bradykinin-Mediated Angioedema (SGBA):; Caballero, T.; Baeza, M. L.; Cabañas, R.; Campos, A.; Cimbollek, S.; Gómez-Traseira, C.; González Quevedo, T.; et al.
Abstract Angioedema refers to a localized, transient swelling of the deep skin layers or the upper respiratory or gastrointestinal mucosa. It develops as a result of mainly two different vasoactive peptides, histamine or bradykinin. Pathophysiology, as well as treatment, is different in each case; nevertheless, the resulting signs and symptoms may be similar and difficult to distinguish. Angioedema may occur at any location. When the affected area involves the upper respiratory tract, both forms of angioedema can lead to an imminent upper airway obstruction and a life-threatening emergency. Emergency physicians must have a basic understanding of the pathophysiology underlying this process. Angioedema evaluation in the emergency department (ED) should aim to distinguish between histamine- and bradykinin-induced angioedema, in order to provide appropriate treatment to patients. However, diagnostic methods are not available at the ED setting, neither to confirm one mechanism or the other, nor to identify a cause. For this reason, the management of angioedema should rely on clinical data depending on the particular features of the episode and the patient in each case. The history-taking should be addressed to identify a possible etiology or triggering agent, recording complete information for an ulterior diagnostic study in the outpatient clinic. It is mandatory quickly to recognize and treat a potential life-threatening upper airway obstruction or anaphylaxis. This review focuses on the underlying mechanisms and management of histamine- and bradykinin-induced angioedema at the emergency department and provides an update on the currently available treatments.